Effects of High Glucose Levels and Glycated Serum on GIP Responsiveness in the Pancreatic Beta Cell Line HIT-T15 - Alessandra Puddu; Roberta Sanguineti; Fabrizio Montecucco; Giorgio Luciano Viviani (Journal of Diabetes Research)
Glucose-dependent insulinotropic peptide (GIP) is an incretin hormone produced in the gastrointestinal tract that stimulates glucose dependent insulin secretion. Impaired incretin response has been documented in diabetic patients and was mainly related to the inability of the pancreatic beta cells to secrete insulin in response to GIP. Advanced Glycation End Products (AGEs) have been shown to play an important role in pancreatic beta cell dysfunction. The aim of this study is to investigate whether the exposure to AGEs can induce GIP resistance in the pancreatic beta cell line HIT-T15. Cells were cultured for 5 days in low (CTR) or high glucose (HG) concentration in the presence of AGEs (GS) to evaluate the expression of GIP receptor (GIPR), the intracellular signaling activated by GIP, and secretion of insulin in response to GIP. The results showed that incubation with GS alone altered intracellular GIP signaling and decreased insulin secretion as compared to CTR. GS in combination with HG reduced the expression of GIPR and PI3K and abrogated GIP-induced AKT phosphorylation and GIP-stimulated insulin secretion. In conclusion, we showed that treatment with GS is associated with the loss of the insulinotropic effect of GIP in hyperglycemic conditions.